Stabilization of planar landslides in permafrost - Pufahl, D. E.; Morgenstern, N. R. (Canadian Geotechnical Journal, 1979)
A method of stabilizing or inhibiting the occurrence of planar landslides in regions of permafrost, utilizing an insulative material and a free-draining surcharge load, is presented. A measure of the pore pressures considered in the effective stress analysis is determined by assuming steady state seepage parallel to the surface and pore water pressures generated during thaw consolidated due to self-weight and surcharge load. The insulation reduces the rate of thaw and thus the rate of generation of excess pore water pressures, and the surcharge increases the effective normal stress disproportionate to any increase in shearing stress.Different design methods are outlined and a series of design charts is proposed for rapid computation of the required combination of insulation thickness and surcharge load for a range of typical soil and climatic conditions encountered in arctic and subarctic regions.